2022
DOI: 10.1002/slct.202201133
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Derived Oxygen‐Rich Carbon with Enhanced Redox Reactions as a Cathode Material for Aqueous Zn‐Ion Batteries

Abstract: Aqueous Zn-ion batteries based on carbon cathode materials show high potential in the application of energy storage due to their low cost, high safety and long cycling lifespan, but the low reversible capacity and energy density hinder their practical. Herein, CO 2 -derived oxygen-rich carbons by molten salt electrolysis are proposed as attractive cathode materials with enhanced redox reactions. By optimizing the electrolysis current density at 50 mA cm À 2 , electrolytic carbon featuring honeycomb-like morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…59,60 This enhancement occurs through the following reactions: C 61,62 Although the oxygen-containing carbons have many advantages for ZICs, only a few works about the CO 2 -C were reported. 15,63 Li and Yang et al reported a CO 2 -derived OMC for ZICs. 15 OMC was innovatively obtained through bidirectional electrolytic reduction of CO 2 in a molten Li 2 CO 3 −Na 2 CO 3 −K 2 CO 3 .…”
Section: Capacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 This enhancement occurs through the following reactions: C 61,62 Although the oxygen-containing carbons have many advantages for ZICs, only a few works about the CO 2 -C were reported. 15,63 Li and Yang et al reported a CO 2 -derived OMC for ZICs. 15 OMC was innovatively obtained through bidirectional electrolytic reduction of CO 2 in a molten Li 2 CO 3 −Na 2 CO 3 −K 2 CO 3 .…”
Section: Capacitorsmentioning
confidence: 99%
“…The overall ZICs performance of carbon materials relies on the proper mesopore structure and surface functional groups, which provide short diffusion paths for enhancing ion and electrolyte transport and pseudocapacitive redox reactions. Surface functionalization of carbons with oxygen-containing functional groups, such as C–OH and CO, is advocated as an ancillary strategy to modulate and amplify the pseudocapacitive behavior of ZICs. , This enhancement occurs through the following reactions: C + X – = X-C (X – : anions) and C–OH + Zn 2+ + 2e = C–O–Zn or C–OH + 2Zn 2+ + e = C–O–Zn + H + . , Although the oxygen-containing carbons have many advantages for ZICs, only a few works about the CO 2 -C were reported. , Li and Yang et al reported a CO 2 -derived OMC for ZICs . OMC was innovatively obtained through bidirectional electrolytic reduction of CO 2 in a molten Li 2 CO 3 –Na 2 CO 3 –K 2 CO 3 .…”
Section: Applications Of Energy Storage and Electrocatalysismentioning
confidence: 99%